An organisational typology of public private engagement for health in Southern Africa: A systematic review - Whyle, Eleanor Beth (Department of Public Health and Family Medicine, 2015)
In Southern Africa, as elsewhere, public-private engagement (PPE) for the provision and financing of healthcare is considered a pervasive and valuable mechanism for meeting the health needs of the population. A wide range of mechanisms for engagement are available, each with organisational models that make them suited to overcoming particular barriers in particular health system contexts. The extent to which a PPE initiative produces the desired outcome is largely dependent on the organisational structure of the collaboration. This study uses scoping and systematic review methods to develop a typology of PPE models visible in Southern Africa and investigate the organisational variations between them. While a variety of PPE models are utilised in the current Southern African context, donor-dependency remains high and there is room to expand engagement of this sort by adopting more innovative mechanisms for engagement and organisational models. An account of the models of PPE being initiated in the Southern African context constitutes a first step toward an analysis of the effectiveness of various mechanisms, and points the way to areas of possible expansion of efforts to engage with the non-state health sector to more effectively align goals in the interest of public health. To some extent, possible models are determined by country context and state capacity. Nonetheless private resources for health, including capital, human resources and technical capacity of for-profit and not-for-profit non-state health sector organisations, represent a rich source of health systems resources that could be more fully utilised through more innovative PPE initiatives for delivery and financing of health care.